Hopf-Pitchfork Bifurcation in a Phytoplankton-Zooplankton Model with Delays - Jia-Fang Zhang; Dan Zhang (Abstract and Applied Analysis)
The purpose of this paper is to study the dynamics of a phytoplankton-zooplankton model with toxin delay. By studying the distribution of the eigenvalues of the associated characteristic equation, the pitchfork bifurcation curve of the system is obtained. Furthermore, on the pitchfork bifurcation curve, we find that the system can undergo a Hopf bifurcation at the positive equilibrium, and we derive the critical values where Hopf-Pitchfork bifurcation occurs.